Security issues in the post-cold war world - Davis, M. Jane, 1950- (Cheltenham, UK : Edward Elgar, 1996)
The end of the Cold War revolutionized East-West relations, yet we still live in an ungoverned world of states which recognize no authority above themselves and whose conduct is minimally restrained by considerations of law and morality. Security Issues in the Post-Cold War World focuses on the changing international security agenda and the serious political instabilities - many rooted in ethnic nationalisms and long-standing border disputes - which have resurfaced with the end of the Cold War. After essays re-examining perennial security problems - including collective security, nuclear proliferation and environmental security - a series of regional studies focuses on the particular problems facing Europe, the Middle East and Southeast Asia. Drawing on a wide body of analysis and research on the international system, the contributors to this volume conclude that, despite the ending of the Cold War, 'security', whether defined narrowly or widely, is a scarce commodity.
Introduction: conflict and security in the 'new world order' / John C. Garnett -- 1. European security after the Cold War / John C. Garnett -- 2. Russian national security policy after the Cold War / Jennifer G. Mathers -- 3. Culture and conflict in the post-Cold War world / Alan Macmillan -- 4. The security of Arab Gulf states and the end of the Cold War: external security versus internal stability / Clive Jones -- 5. 'The perils of prosperity?' Security and economic growth in the ASEAN region / Amitav Acharya and Richard Stubbs -- 6. The United Nations: collective security and individual rights / Justin Morris -- 7. Security, nuclear proliferation and the end of the Cold War / Nicholas J. Wheeler and Simon J. Davies -- 8. Environmental security / Rowland T. Maddock -- 9. The security dilemma / Alan Collins -- 10. 'Travel without maps': thinking about security after the Cold War / Richard Wyn Jones.
Includes bibliographical references (p. 219-237) and index.
Keywords: Security, International; World politics -- 1989-